The Quality of Learning in Mu’adalah Boarding School - Hairul Huda; Siti Nursyamsiyah; Bahar Agus Setiawan (Jurnal Pendidikan Islam Indonesia, 2022)
Recognition of Islamic boarding schools shows a stronger existence with updates and changes to the system, also supported by government policies with the term mu’adalah. The level of learning independence that was the potential of the mu’adalah Islamic boarding school students was the result of the construction of a comprehensive learning implementation system. The totality from the planning stage to implementation was a reflection of the quality of learning in mu’adalah Islamic boarding schools. The transformation and modernization of the mu’adalah Islamic boarding school were marked by the quality assurance of teaching staff starting from the aspects of qualifications and competencies aligned with government policies. The embodiment of the quality of learning mu’adalah was competence. The reflection of this description forms the basis that the purpose of this study was to look comprehensively at the quality of learning in the mu’adalah Islamic boarding school. This research took place at the Baitul Arqom mu’adalah Islamic boarding school and used a qualitative approach with the main respondents being ustadz, students, and boarding school administrators. The results of the study showed the quality of learning at Baitul Arqom Islamic Boarding School due to the evaluation of the implementation of the learning process in stages from weekly to the end of each semester. As for the evaluation of student learning, written tests, oral tests, and practice were carried out consistently with original assessments.